Bimbingan Pra Nikah: Investasi Terbaik untuk Masa Depan Bersama - Fikfik Taufik; Yudi Daryadi; Mochamad Faizal Almaududi Aziz Dachlan; Indra Budi Jaya; Widaningsih Widaningsih; Salma Rizky Salsabila; Dinda Lovia Nasution; Luqman Nurrahman (Pusat Riset dan Inovasi Nasional, 2024)
The Islamic Family Law Study Program at Universitas Muhammadiyah Bandung on Thursday, July 18, 2024 had the opportunity to carry out one of the tridarma of higher education, namely community service. The community service carried out by the Islamic Family Law Study Program of Universitas Muhammadiyah Bandung is by contributing and synergizing with the Cilengkrang District Religious Affairs Office in Marriage Guidance activities, by becoming one of the facilitators in the activity. In general, the structure of the Marriage Guidance activities is as follows; 1) Registration and Tetanus Vaccination for female participants, 2) Opening of Marriage Guidance Activities, 3) Remarks on Marriage Guidance Activities, 4) Health and Tetanus Material from a Medical Perspective, 5) Reproductive Health Material from an Islamic Law perspective, 6) Marriage Advice, 7) Closing of Marriage Guidance Activities, 8) Handover of certificates to participants, 9) Documentation. This Marriage Guidance activity is held to provide provisions for prospective brides who will enter the world of marriage. This activity, contains a lot of advice, messages, and insights that are expected to help prospective brides when facing problems that arise in the household ark.